How to Treat Hypertension in Patients With Coronary Heart Disease disease. - Moser, Marvin (J Clin Hypertens (Greenwich), 2008)
Following a hypertension symposium in Los Angeles in October 2007, a panel was convened to discuss how to treat hypertension in patients with coronary artery disease or with evidence of multiple major risk factors for coronary heart disease. Marvin Moser, MD, Clinical Professor of Medicine at the Yale University School of Medicine, New Haven, CT, moderated the discussion. Jackson T. Wright Jr, MD, PhD, Professor of Medicine, Program Director of William T. Dahms Clinical Research, and Director of the Clinical Hypertension Program at Case Western Reserve University, Cleveland, OH; Ronald G. Victor, MD, Professor and Division Chief, Hypertension, University of Texas Southwestern Medical Center, Dallas, TX; and Joel Handler, MD, Hypertension Lead, Care Management Institute, Kaiser Permanente, Anaheim, CA, participated in the discussion.